"In vitro" surface roughness of different glass ionomer cements indicated for ART restorations - Marília Gabriela Corrêa Momesso; Renata Cristiane da Silva; José Carlos Pettorossi Imparato; Celso Molina; Ricardo Scarparo Navarro; Sidney José Lima Ribeiro (Universidade Estadual de Campinas, 2015)
Aim: The aim of this in vitro study was to evaluate the surface roughness of three glass ionomer cements (GICs) indicated for ART restorations. Methods: Ten cylindrical specimens of three commercial glass ionomers cements (Vidrion R - S.S. White, Maxxion R - FGM and Vitromolar DFL) were prepared (n=30) without surface finishing or protection. Twenty-four hours after preparation, the surface roughness measurements were obtained as the mean of three readings of the surface of each specimen by profilometry. The roughness values (Ra, µm) were subjected to one-way ANOVA and Tukey's test (p<0.05). Results: No statistically significant differences were observed between Vidrion R (0.18 ± 0.05) and Vitromolar (0.21 ± 0.05), whereas Maxxion R presented significantly higher roughness values than those of the other materials. Conclusions: It may be concluded that characteristics of particle size and composition of the different GICs affected their surface roughness 24 h after preparation.